FACTORS AFFECTING TO CONSUMERS LOYALTY OF LOW COST GREEN CARS - Taufik Zulfikar; Eva Rachmawati (Jurnal Manajemen Indonesia, 2018)
Automotive industrial competition in Indonesia is becoming tighter. Various types of cars are offered by the producers to the consumers for all segments. One of the types of the cars penetrated to the market in Indonesia is of the concepts of Low Cost and Green Car (LCGC) for the middle and lower segments. The customer relationship is the most important variable to maintain the customer loyalty. A good brand image can also be the supporting factor to keep them loyal. This study aims to determine the impact of relationship management and brand image to customer loyalty. This study was conducted through survey method, and data was collected from 400 vehicles owners. This paper used Structural Equation Modelling (SEM) to analysis. The result of the study shows that the customer relationship management and brand image impact simultaneously and partially to customer loyalty. Keywords—Brand Image; Customer Loyalty; LCGC; Relationship Management. Abstrak Persaingan industri otomotive di Indonesia semakin ketat. Berbagai jenis mobil ditawarkan produsen kepada konsumen semua segmen. Salah satu jenis mobil adalah low cost and green car (LCGC) untuk segmen menengah ke bawah. Kerelasian pelanggan merupakan variabel penting untuk mempertahan loyalitas pelanggan. Citra merek yang baik dapat juga menjadi pendorong pelanggan tetap loyal. Penelitian ini bertujuan untuk mengetahui pengaruh manajemen hubungan dan citra merek terhadap loyalitas pelanggan. Penelitian ini menggunakan metode survey dan data diperoleh dari 400 orang pemilik. Alat analisa yang digunakan adalah Structural Equation Modeling (SEM). Hasil penelitian menunjukkan bahwa terdapat pengaruh manajemen hubungan pelanggan dan citra merek terhadap loyalitas pelanggan baik secara simultan maupun secara parsial. Kata Kunci—Citra Merek; Loyalitas Pelanggan; LCGC; Manajemen Kerelasian.